2015
DOI: 10.1038/ncomms7232
|View full text |Cite
|
Sign up to set email alerts
|

Multimode optomechanical dynamics in a cavity with avoided crossings

Abstract: Cavity optomechanics offers powerful methods for controlling optical fields and mechanical motion. A number of proposals have predicted that this control can be extended considerably in devices where multiple cavity modes couple to each other via the motion of a single mechanical oscillator. Here we study the dynamic properties of such a multimode optomechanical device, in which the coupling between cavity modes results from mechanically induced avoided crossings in the cavity's spectrum. Near the avoided cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 44 publications
3
65
1
Order By: Relevance
“…Nonlinearities can also arise from spatial, mechanical effects, by engineering, for example, a light-matter interaction of the form (â+â † )(G 1x +G 2x 2 ). Previous studies investigated the static shift in the cavity resonant frequency [9,14,15] or the quadratic optical spring effect [15] arising from a nonlinear coupling. However, these studies identified the problem of a residual linear G 1 contribution to the coupling.…”
mentioning
confidence: 99%
“…Nonlinearities can also arise from spatial, mechanical effects, by engineering, for example, a light-matter interaction of the form (â+â † )(G 1x +G 2x 2 ). Previous studies investigated the static shift in the cavity resonant frequency [9,14,15] or the quadratic optical spring effect [15] arising from a nonlinear coupling. However, these studies identified the problem of a residual linear G 1 contribution to the coupling.…”
mentioning
confidence: 99%
“…[5,6]. More broadly, the particular type of oscillator used here (a Si 3 N 4 membrane) has been shown to be well suited to a range of applications in quantum optomechanics [8,9,[20][21][22][23][24][25][26][27][28].In the experiments described here, both sidebands are produced by a single laser and are measured simultaneously. This is in contrast with most earlier experiments, in which the sidebands were produced using two separate drives applied at once [16,19] or at different times [17,13].…”
mentioning
confidence: 99%
“…[5,6]. More broadly, the particular type of oscillator used here (a Si 3 N 4 membrane) has been shown to be well suited to a range of applications in quantum optomechanics [8,9,[20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Recent experiments have measured QOC in various optomechanical setups such as membrane in the middle set-up [28][29][30][31], atomic gases trapped in Fabry-Prot cavities [32], microdisk-cantilever systems [33], microsphere-nanostring systems [34], paddle nanocavities [35] and tunable photonic crystal Optomechanical Cavity [36,37]. Among all these schemes the tunable photonic crystal system enabled to yield the value of QOC of 245 Hz [36] and the recent advancement has pushed this limit to the order of kHz [37].…”
Section: Introductionmentioning
confidence: 99%